Strategi Komunikasi Guru Pendidikan Agama Dalam Membentuk Akhlak Mulia Peserta Didik Di Madrasah Tsanawiyah - Zakaria Zakaria (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study aims to: (1) to determine the communication of religious teachers at MTs Pompanua District of Ajangale Bone district, (2) to determine the character of students MTs Pompanua Kec. Ajangale Kab. Bone, and (3) to determine the impact of communication teachers of religion in shaping the morals noble students at MTs PompanuaAjangale Kec. Ajangale Kab. Bone. This research is a qualitative descriptive nature. The results showed: (1) a religious teacher at MTs Pompanua District of Ajangale Regency Bone implement the communication patterns in many directions in the learning activities, (2) the character of students MTs Pompanua Kec. Ajangale Kab. Bone is quite good, it is supported by coaching programs conducted by the madrassa, and (3) the communication of teachers of religion in shaping the noble character of students at MTs Pompanua Kec. Ajangale Kab. Bone positive impact in improving the morals of learners.